Jugun Ianfu: The Darkest History of Human Rights Violation - Ghina Elmira (The Indonesian Journal of International Clinical Legal Education, 2020)
World War II leaves a sad story for some colonies and occupations, Indonesia which has been colonized by 350 years by the Dutch continuing 3.5 years of Japanese occupation that impact on the development of Indonesia. The painful story of slavery during the Japanese period cannot be separated from the Occupation at that time. The women who have no sin in them get the promise of getting a job, singing, or wrestling in the theater, to follow their wishes that are mere promises of physical and psychological violence that threaten the young women of Indonesia.